2001
DOI: 10.1007/s004200100267
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence and work place exposure among Swedish biomedical research personnel

Abstract: In general, there were few cases of cancer in this comparatively young cohort, but the findings give some indication of increased risks for malignant melanoma in female laboratory personnel after exposure to organic solvents or substances classified by IARC as being possibly carcinogenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…A large population-based casecontrol study in British Columbia reported increased risks in occupations that used solvents and pesticides [Band et al, 2000]. A slight increase in breast cancer incidence was observed among women who were employed in biochemical research laboratories, concluding that increase may be due 1980-1984 1985-1988 1989-1992 1993-1996 to laboratory chemical exposure [Wennborg et al, 2001]. In industries that used solvents, a significant increase in risk for breast cancer was reported among young women (OR 1.3, P < 0.05) when exposure was categorized by the length of employment in a particular industry [Hansen, 1999].…”
Section: Discussionmentioning
confidence: 96%
“…A large population-based casecontrol study in British Columbia reported increased risks in occupations that used solvents and pesticides [Band et al, 2000]. A slight increase in breast cancer incidence was observed among women who were employed in biochemical research laboratories, concluding that increase may be due 1980-1984 1985-1988 1989-1992 1993-1996 to laboratory chemical exposure [Wennborg et al, 2001]. In industries that used solvents, a significant increase in risk for breast cancer was reported among young women (OR 1.3, P < 0.05) when exposure was categorized by the length of employment in a particular industry [Hansen, 1999].…”
Section: Discussionmentioning
confidence: 96%
“…Depending on the chemicals to be exposed, low level exposure does not imply that there is no health risk. It was reported that, although the risk appears to be generally low, the incidence may be increased for some types of malignancy [1][2][3][4] among laboratory personnel who use e.g. carcinogens and mutagens.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects of foregoing studies on occupational health in laboratories were mostly on either carcinogenicity [1][2][3][4] or reproductive toxicity 5) among staff exposed to chemicals in laboratories, with limited data on types of chemicals used or intensity of exposures.…”
Section: Introductionmentioning
confidence: 99%
“…[Sasco, 1992;Wennborg et al, 2001a]. The questionnaire included information about methods/techniques and agents used by the members of the research groups.…”
Section: Exposure Assessmentmentioning
confidence: 99%